A bibliometric review of coach leadership studies - Cruz, Angelita Bautista; Kim, Hyun-Duck (Frontiers in Psychology, 2023)
This study examined published articles concerning sports leadership within the sport psychology domain over the last 30 years using bibliometric analysis that centered on the written content of the publications as unit of analysis in order to explore the intellectual base, particularly the structural relationships among relevant research components about coach leadership. Leximancer version 5.0 (Leximancer Pty Ltd.) was used to extract data from 100 sports leadership-related articles from four sport psychology journals. Overall, the most relevant concepts generated were coaches (100%) and athletes (59%), followed by study, sport, support, and motivation, and behaviors. Also, relevant concepts produced for each journal were quite similar which included coaches, athletes, behaviors, study, support and team. Further, publications related to coach leadership have shown a steady growth rate since 1990 with 76% of all published articles were conducted via quantitative research method. Finally, United States, Canada, the United Kingdom, and Belgium were the top countries involved in the area of coach leadership. Coach leadership studies generally focus on behaviors and perceptions related to the coach and relationships between leadership and psychological outcomes. Each journal has a similar but distinct rationale when publishing papers about coach leadership. Bibliometric analysis can be applied as an alternative methodology to summarize large volumes of relevant data in order to map the current knowledge as well as identify potential future research directions.